Investment Climate Around the World : Voices of the Firms from the World Business Environment Survey - Batra, Geeta (Washington, DC: World Bank, 2013)
The analysis of firm-level data collected through parallel international enterprise surveys can reveal important linkages between governance constraints and business growth and investment. The World Business Environment Survey (WBES), an initiative led by the World Bank Group in 1999 and 2000, collected enterprise data from more than 10,000 firms in 80 countries. Econometric analysis of responses to that survey points to a strong association between corruption, financing, regulatory and tax constraints, policy uncertainty, and protection of intellectual property rights with firm-level performance, as measured by sales and investment growth and participation in the formal economy. This book present the core WBES questionnaire and survey findings, and confirms the significance of key country conditions on the firm performance and behavior. The finding provide a basis for regional comparison, but suggest the need for caution when averaging across categories, especially in light of country conditions that can significantly affect firm-level sales and investment.